The Value of Character Education in Tembang Dolanan Jawa and Its Implementation in The Cultural Art Learning Process - Lathifasari, Meisera Fika; Widodo, Widodo; Wadiyo, Wadiyo (Catharsis, 2021)
One of the arts that is very full of Islamic nuance with the Kikim Tribe is the art of “Arakan” or "Ngarak" (parade) or better known as the Kikim bridal parade. The problem raised in this study aims to analyze the music of the Kikim bridal parade as a cultural expression of the Kikim Tribe in Lahat Regency. This research used a qualitative method with a case study research design. Data collection techniques involved observation, interviews and document studies. The results showed that the Arakan which was staged in Kikim District, Padang Bindu Village, was a form of cultural expression for the Kikim community living in Lahat Regency. The performance is often staged for accompanying the bride and groom from Kikim Tribe In the organological framework, Ngarak or Arakan music consists of compositions of poetry (vocals), tambourines (rhythm), tambourines/terbangan genjring (rhythm), and gongs (rhythm). Meanwhile, if they are classified based on the characteristics of instruments used, they fall into the category of percussion instruments. The songs in Arakan use sholawat and berzanji lyrics (prays and praises for Prophet Muhammad SAW) and they are performed by dancers (as well as vocals). Therefore, the role of vocals in Arakan is to play the melody of the song sung by the dancers to clarify the meaning of the song through poetry in addition to providing an element of aesthetic variation.